The Impact of Eliminating National Examinations on Educa-tional Evaluation Quality in Indonesia: A Policy Analysis on Equity and Accountability (International Journal of Education and Literature, 2025)
The abolition of the National Examination (UN) as a national policy has marked a significant change in the education evaluation system in Indonesia. This policy was implemented with the aim of reducing psychological pressure on students and replacing it with a more holistic evaluation approach through the National Assessment (AN). However, this transformation has raised various issues, particularly regarding the aspects of equity and accountability in education quality. This study aims to analyze in depth the impact of the abolition of UN on the quality of educational evaluation by examining its implications for equitable access, fairness, and accountability systems at both national and local levels. This research uses a qualitative method with a Systematic Literature Review (SLR) approach, analyzing various scholarly literature sources and relevant policy documents published between 2020 and 2024. The findings indicate that although the UN was abolished with the intention of promoting fairness and reducing academic stress, the implementation of AN has yet to ensure equitable implementation of educational evaluations across regions. Moreover, the absence of a standardized, open, and quantitative evaluation indicator such as the UN has weakened transparency and accountability in education, both in the public's perception and in policy-making processes. Therefore, a new evaluation system is needed—one that is not only diagnostic in nature but also ensures data transparency, equitable access, and strengthened public accountability functions in education.